Tag team - Raúl the Third, 1976- (Raúl the Third, 1976- Toro & friends., 2021)
Luchadore star El Toro teams up with his fighting partner, La Oink Oink, when a post-match mess at the stadium becomes a bit too intimidating to clean up alone.